Peningkatan Pendapatan Ekonomi Masyarakat Melalui Pelatihan Perbaikan Pengelolaan Motivasi Wirausaha, Produk & Kemasan UMKM RW 15 Kampung Sejahtera Mandiri (KSM) Teras Pancasila Binaan Dinas Koperasi & UMKM Kota Tangerang, Provinsi Banten - Silaban, Berlin; Yanti, Lia Dama; Simbolon, Sabam; Tholok, Fidellis Wato; Sugandha, Sugandha; Herijawati, Etty (LP3kM Universitas Buddhi Dharma, 2021)
The potential for developing and fostering an entrepreneurial spirit for the younger generation in RW 15, Kampung Sejahtera Mandiri (KSM) Teras Pancasila, which is assisted by the Office of Cooperatives & MSMEs, Tangerang City, Banten Province, is enormous. One of the reasons for its strategic location as the entrance route to the west of Jakarta. However, the development and fostering of entrepreneurial spirit is still not optimal because the level of education of most of the target audience is high school graduates who rarely or may never get knowledge of entrepreneurship and business management. Many potential creative ideas for running a business have not been explored optimally either. The purpose of this MSME Management Management Improvement Training is expected to foster the entrepreneurial spirit of the young generation so that they always have thoughts of improving their own business by making good use of existing resources and capital to create products, innovating packaging of goods that have economic value. For those who have not started it are expected to be more courageous in opening various businesses but in a well-planned manner